Analiza czynników ryzyka w przedsięwzięciu innowacyjnym na wybranym przykładzie - Knosala, Ryszard; Landwójtowicz, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Risk is often understood as an adverse event. It has to be remembered however, that despite of common understanding and use, the risk may also refer to positive phenomenon. Resignation of risk could mean a potential loss of benefits that arise from project implementation (subjected to high risk). Implementation of innovations is connected with a high degree of risk, mainly because of high implementation costs and its long time horizon. The risk connected with innovations is perceived as a product of probability of an occurrence of event and its results (loss). In order to minimise negative effects of the undertaking, a classification of its sources and interrelation has to be made. It is also important to set the level of accepted risk and evaluation of related financial consequences. Furthermore, it is vital to define a preventive action and choice of funding sources for risky enterprises. The study presents a hypothetical risk analysis process of innovation implemented by agricultural enterprise, using a technical-manufacturing risk map. Risk mapping is a method that enables to illustrate the probability of occurrence of an event and its consequences in order to determine priority actions leading to reduction of the negative effects of a given event. As far as the creation of the balance sheet is concerned, a given undertaking and sources of its risk are divided into three fields: high risk, medium risk and low risk. The procedure of risk management should aim to eliminate factors located in a high risk area and move towards the area of low risk (in accordance with the assumption that a total elimination of risk is impossible).